Generative AI : unlocking the next chapter in healthcare - Mahajan, Rohit; Uberoy, Ritu M. (Productivity Press, 2026)
From algorithms that draft clinical notes in seconds to autonomous agents that triage emergency room backlogs, artificial intelligence is quietly reshaping every facet of healthcare.